Three Nightmare Traits in Leaders - de Vries, Reinout E. (Frontiers in Psychology, 2018)
This review offers an integration of dark leadership styles with dark personality traits. The core of dark leadership consists of Three Nightmare Traits (TNT)—leader dishonesty, leader disagreeableness, and leader carelessness—that are conceptualized as contextualized personality traits aligned with respectively (low) honesty-humility, (low) agreeableness, and (low) conscientiousness. It is argued that the TNT, when combined with high extraversion and low emotionality, can have serious (‘explosive’) negative consequences for employees and their organizations. A Situation-Trait-Outcome Activation (STOA) model is presented in which a description is offered of situations that are attractive to TNT leaders (situation activation), situations that activate TNT traits (trait activation), and the kinds of outcomes that may result from TNT behaviors (outcome activation). Subsequently, the TNT and STOA models are combined to offer a description of the organizational actions that may strengthen or weaken the TNT during six career stages: attraction, selection, socialization, production, promotion, and attrition. Except for mainly negative consequences of the TNT, possible positive consequences of TNT leadership are also explored, and an outline of a research program is offered that may provide answers to the most pressing questions in dark leadership research.